Fatty Amides from Crude Rice Bran Oil as Green Corrosion Inhibitors - E. Reyes-Dorantes; J. Zuñiga-Díaz; A. Quinto-Hernandez; J. Porcayo-Calderon; J. G. Gonzalez-Rodriguez; L. Martinez-Gomez (Journal of Chemistry)
Due to its high oil content, this research proposes the use of an agroindustrial byproduct (rice bran) as a sustainable option for the synthesis of corrosion inhibitors. From the crude rice bran oil, the synthesis of fatty amide-type corrosion inhibitors was carried out. The corrosion inhibitory capacity of the fatty amides was evaluated on an API X-70 steel using electrochemical techniques such as real-time corrosion monitoring and potentiodynamic polarization curves. As a corrosive medium, a CO2-saturated solution (3.5% NaCl) was used at three temperatures (30, 50, and 70°C) and different concentrations of inhibitor (0, 5, 10, 25, 50, and 100 ppm). The results demonstrate that the sustainable use of agroindustrial byproducts is a good alternative to the synthesis of environmentally friendly inhibitors with high corrosion inhibition efficiencies.